A prospective study of pediatric and adolescent renal cell carcinoma: A report from the Children's Oncology Group AREN0321 study. Issue 23 (14th September 2020) - Geller, James I.; Cost, Nicholas G.; Chi, Yueh‐Yun; Tornwall, Brett; Cajaiba, Mariana; Perlman, Elizabeth J.; Kim, Yeonil; Mullen, Elizabeth A.; Glick, Richard D.; Khanna, Geetika; Daw, Najat C.; Ehrlich, Peter; et al.
Abstract : Background: To the authors' knowledge, AREN0321 is the first prospective clinical study of pediatric and adolescent renal cell carcinoma (RCC). Goals of the study included establishing epidemiological, treatment, and outcome data and confirming that patients with completely resected pediatric RCC, including lymph node–positive disease (N1), have a favorable prognosis without adjuvant therapy. Methods: From 2006 to 2012, patients aged <30 years with centrally reviewed pathology of RCC were enrolled prospectively. Results: A total of 68 patients were enrolled (39 of whom were male; median age of 13 years [range, 0.17‐22.1 years]). Stage was classified according to the American Joint Committee on Cancer TNM stage seventh edition as stage I in 26 patients, stage II in 7 patients, stage III in 26 patients, and stage IV in 8 patients, and was not available in 1 patient. Sixty patients underwent resection of all known sites of disease, including 2 patients with stage IV disease. Surgery included radical nephrectomy (53 patients [81.5%]), partial nephrectomy (12 patients [18.5%]), and unknown (3 patients [4.4%]). Histology was TFE‐associated RCC (translocation‐type RCC; tRCC) in 40 patients, RCC not otherwise specified and/or other in 13 patients, papillary RCC in 9 patients, and renal medullary carcinoma (RMC) in 6 patients. Lymph node status was N0 in 21 patients, N1 in 21 patients (tRCC in 15 patients, RMC in 3 patients, papillary RCC in 2 patients, and not otherwise specified and/or other in 1 patient), and Nx in 26 patients. The 4‐year event‐free survival and overall survival rates were 80.2% (95% CI, 69.6%‐90.9%) and 84.8% (95% CI, 75.2%‐94.5%), respectively, overall and 87.5% (95% CI, 68.3%‐100%) and 87.1% (95% CI, 67.6%‐100%), respectively, for the 16 patients with N1M0 disease. Among patients presenting with metastases, 2 of 8 patients (2 of 5 patients with RMC) were alive (1 with disease) at the time of last follow‐up, including 1 patient who was lost to follow‐up (succinate dehydrogenase deficiency). The predominant RCC subtypes associated with mortality were tRCC and RMC. Conclusions: Favorable short‐term outcomes can be achieved without adjuvant therapy in children and adolescents with completely resected RCC, independent of lymph node status. A prospective study of patients with tRCC and RMC with M1 or recurrent disease is needed to optimize treatment. Abstract : The current prospective clinical trial confirms that favorable outcomes can be achieved without adjuvant therapy in children and adolescents with completely resected renal cell carcinoma, independent of lymph node status. Prospective study of translocation renal cell carcinoma and renal medullary carcinoma with metastatic or recurrent disease is needed to optimize treatment.